Experimental investigation using vibration testing method to optimize feed parameters of color mixing nozzle for fused deposition modeling color 3D printer. (December 2019) - Li, Zhiyong; Zhang, Dawei; Shao, Liangchen; Han, Shanling
To improve the blockage and printing quality of the color mixing nozzle of fused deposition modeling color 3D printer, the feed parameters of fused deposition modeling color 3D printer were studied by vibration test. The acceleration sensor was fixed up the color mixing nozzle to analyze the vertical vibration of the nozzle. The vibration test of different feed speed, torque, and material were performed under the actual printing condition. Vertical vibration of the nozzle was characterized by an acceleration sensor. The comparative analysis of the actual testing results indicates that the optimum feed parameters are feed torque of triple torque extruder, feed speed of 20 mm/s, and feed material of ABS. Further analysis shows that higher feed torque can be used to improve the printing quality of the color mixing nozzle. The appropriate feed speed of the color 3D printer can not only reduce the accumulation of wire material at a lower speed but also reduce the blockage caused by too-high feed speed. It is proposed that the feed material with smaller flow behavior index and no phase transition in the melting process shows smaller vibration acceleration amplitude.